Socialising the biomedical turn in HIV prevention - Kippax, Susan; Stephenson, Niamh (Key issues in modern sociology., 2016)
This book addresses the major challenge for HIV prevention: that is, to reach beyond the limitations of biomedical approaches to disease and to design prevention strategies informed by and connected with the social realities of people's lives.